Hybrid Graphenene Oxide/Cellulose Nanofillers to Enhance Mechanical and Barrier Properties of Chitosan-Based Composites - Santillo, C.; Wang, Yinglei; Buonocore, G. G.; Gentile, G.; Verdolotti, L.; Kaciulis, Saulius; Xia, H.; Lavorgna, M. (Frontiers in Chemistry, 2022)
Chitosan-based hybrid nanocomposites containing cellulose nanocrystals (CNCs), graphene oxide (GO) and borate as crosslinking agent were successfully prepared by the solution-casting technique. The synergistic effect of the two fillers, as well as the role of the crosslinker, in enhancing the structural and functional properties of the chitosan polymer, was investigated. The morphological characterization shows that the GO sheets are oriented along the casting surface, whereas the CNC particles are homogenously distributed in the sample. Results of tensile tests reveal that the presence of graphene oxide enhances the elastic modulus, tensile strength, elongation at break and toughness of chitosan, while cellulose and borate induce an increase of the elastic modulus and stress at the yield point. In particular, the elongation at break and toughness of the borate-crosslinked chitosan-based sample containing 0.5 wt% of GO and 0.5 wt% of CNCs significantly increase by 124% and 216% respectively, compared to the pristine polymer. Moreover, the water permeability results show that the presence of graphene oxide slightly increases the water barrier properties, whereas the borate and cellulose nanocrystals significantly reduce the water vapour permeability of the polymer of about 50%. Thus, by modulating the content of the two reinforcing fillers, it is possible to obtain chitosan-based nanocomposites with enhanced mechanical and water barrier properties which can be potentially used in various applications such as food and electronic packaging.